2022
DOI: 10.1097/md.0000000000030005
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the clinical and pathological features of hepatic sarcomatoid carcinoma: Fourteen cases of a rare tumor

Abstract: Hepatic sarcomatoid carcinoma is a rare liver malignancy with atypical clinical symptoms and a high degree of malignancy. To improve the understanding of this disease, we collected the clinical and pathological data of 14 patients with hepatic sarcomatoid carcinoma admitted to the First Affiliated Hospital and Second Affiliated Hospital of Bengbu Medical College from 2011 to 2021 and reviewed the relevant literature.The clinical and pathological data of 14 patients with hepatic sarcomatoid carcinoma were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Both HS HSC are rare tumor with high malignancy and poor prognosis [1,5,11] In our study, we did not nd any signi cant difference between the two tumors in the tumor markers, such as AFP, CEA and CA1-99. This is consistent with previous ndings that tumor markers are non-speci c [11,12,14] .Meanwhile, we found signi cant differences between the hepatitis and cirrhotic backgrounds of the two tumor. In our study, 11 patients with HSC had 6 cases of hepatitis (54.5%) and 6 cases of cirrhosis (54.5%), while 12 patients with HS had 0 cases of hepatitis (0%) and 1 case of cirrhosis (8.3%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Both HS HSC are rare tumor with high malignancy and poor prognosis [1,5,11] In our study, we did not nd any signi cant difference between the two tumors in the tumor markers, such as AFP, CEA and CA1-99. This is consistent with previous ndings that tumor markers are non-speci c [11,12,14] .Meanwhile, we found signi cant differences between the hepatitis and cirrhotic backgrounds of the two tumor. In our study, 11 patients with HSC had 6 cases of hepatitis (54.5%) and 6 cases of cirrhosis (54.5%), while 12 patients with HS had 0 cases of hepatitis (0%) and 1 case of cirrhosis (8.3%).…”
Section: Discussionsupporting
confidence: 93%
“…For HS, the imaging presentation is heterogeneous within each kind of HS or between different kinds of HS [31] . Therefore, the diverse pathological classi cation of HS determines its enhancement pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, certain reports have suggested that infections with hepatitis B/C viruses may contribute to sarcomatoid transformation ( 6 , 13 15 ). However, an increasing number of reports on SHC indicate no history of treatment with anticancer or antiviral agents ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the CT/magnetic resonance imaging scan, SHC usually presents as a large mass with an uneven density/signal, peripheral enhancement, central necrosis, variable enhancement of the solid portion with or without the tumor capsule, and intrahepatic metastasis ( 17 , 19 , 20 ). The CT scan in our case showed the mass to be located in the posterior lobe of the liver (right side).…”
Section: Discussionmentioning
confidence: 99%